The Story of a China Cat - Hope, Laura Lee; Smith, Harry L. (Illustrator) (Salt Lake City, UT : Project Gutenberg, 2006)
"The Story of a China Cat" by Laura Lee Hope is a children's novel written in the early 20th century. It follows the enchanting adventures of a white China cat named Snowball who comes to life in a toy shop and dreams of finding a kind owner. The story presents themes of friendship, loyalty, and the whimsical world of toys, highlighting the experiences and mishaps that unfold as Snowball navigates various challenges, including escaping the aftermath of a fire and even a flood. At the start of this delightful tale, readers are introduced to a lively assortment of toys in a dark toy shop, including a Talking Doll and a Trumpeter, who joyfully come to life at night. The narrative kicks off with a fun night of play among the toys, but soon takes a dramatic turn when the shop is threatened by a fire. The China Cat, who expresses her worries about becoming dirty, ends up rescued from the chaos by a young boy named Jeff. However, Jeff's rough handling takes her into a less-than-ideal home setting, resulting in a series of adventures that challenge her tidy nature. Ultimately, Snowball$1 (Bs journey leads her to a new owner, a nice little girl named Jennie, where she can finally enjoy the comfort of a loving home, setting the stage for further delightful escapades. (This is an automatically generated summary.)s
Release date is 2006-09-19
E-text prepared by Marilynda Fraser-Cunliffe, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Toys -- Juvenile fiction; Cats -- Juvenile fiction